RETARDASI MENTAL RINGAN DENGAN EPISODE PSIKOSIS SEBUAH LAPORAN KASUS - Agus Setiawan, I Kadek (E-Jurnal Medika Udayana; vol 3 no 3 (2014):e-jurnal medika udayana, 2014)
Mental Retardation is the decrease of intellectual function thoroughly which occour in development phase and related with social adaptation disturbance. Whereas psychosis is disturbance of personality (mental) function in assess reality, relationship, perception, persons perceptive and effective conception to certain standard, so that improbability to getting tasks done satisfyingly. Frequency of mental retardation occur approximately 1-3% in all population in United State. Although low of incident, investigation about mental retardation is still needful. This report discuss about mental retardation with psychosis episode at female 18 years old which show an eccentric and austistic. In psychiatry examination found with general impression patient with unfair appearance, grimace, less verbal and visual contact with examiner (no attention in anamnesis), autistic, purify consciousness, mood/affect inadequate/blunt. In sensorium examination and cognition found less concentration and attention with speak poorly and presence encouragement instingtualy as hypobulia
Keywords: Mental retardation, psychosis episode